23 The influence of collateral regression post coronary chronic total occlusion (cto) percutaneous coronary intervention (pci) on donor vessel coronary pressure-derived measurements. (5th June 2017) - Mohdnazri, Shah; Al-Janabi, Firas; Karamasis, Grigoris; Hampton-Till, James; Al-Lamee, Rasha; Dungu, Jason; Gedela, Swamy; Tang, Kare; Kelly, Paul; Davies, Justin; Davies, John; Keeble, Thomas
Abstract : Background: There is strong evidence of FFR guided treatment in multi-vessel disease. The presence of a concomitant CTO may influence the FFR measurement in donor vessel as suggested in previous studies and reports. This has an important implication on clinical decision making for complete revascularisation in patients with chronic total occlusion. We sought to investigate the influence of collateral regression after successful CTO recanalisation on donor vessel pressure-derived indices. Methods: The study participants were patients with angina who had RCA CTO. 28 out of 34 consecutive patients underwent successful PCI to RCA CTOs during the study period and completed the follow study (at 3 months post CTO PCI) were included in this analysis. Coronary pressure-derived indices (resting PD/PA, iFR and FFR) were measured pre and post successful RCA CTO PCI in donor vessels and at follow up procedures. Results: The mean age was 62.38 years. The mean estimated CTO duration was 238.72 weeks and CTO length was 32.44 mm. 25 patients had ischaemia and or viability in the RCA territory assessed with cardiac MRI. LAD was the major donor vessel in 24 patients and LCX was the minor donor vessel in 4 patients. Percent stenosis on QCA in the major and minor donor vessel were 40.6% and 35.1% respectively. The mean resting Pd/Pa, iFR and FFR pre and post RCA CTO PCI and at follow-up procedures in major donor vessel were (0.893, 0.862, 0.764), (0.907, 0.886, 0.753) and (0.918, 0.901, 0.787) respectively. The mean resting Pd/Pa, iFR and FFR pre and post RCA CTO PCI and at follow-up procedures in minor donor vessel were (0.979, 0.966, 0.890), (0.983, 0.979, 0.880) and (0.981, 0.974, 0.898) respectively. The changes in coronary pressure-derived indices pre and post RCA CTO PCI and at follow up procedures are summarised in table 1. In major donor vessel, there was significant changes in the difference between follow up and pre-CTO PCI values for Pd/Pa, iFR and FFR values (p values 0.006, 0.003 and 0.047 respectively). There was also significant change in the difference between follow up and post-CTO PCI FFR value (P value 0.002). FFR collateral reduced significantly at follow-up (p value 0.000). Conclusion: Successful recanalisation of a RCA CTO results in increase in major donor vessel coronary pressure-derived indices at follow up procedure associated with the regression of collateral function. In patients with multi-vessel disease, the expected change and the optimal timing to perform PCI in donor vessel should be considered when planning multi-vessel revascularisation in this setting.